2021
DOI: 10.1287/mnsc.2019.3576
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Many: Partner Exposure and Team Familiarity in Fluid Teams

Abstract: In services where teams come together for short collaborations, managers are often advised to strive for high team familiarity so as to improve coordination and consequently, performance. However, inducing high team familiarity by keeping team membership intact can limit workers’ opportunities to acquire useful knowledge and alternative practices from exposure to a broader set of partners. We introduce an empirical measure for prior partner exposure and estimate its impact (along with that of team familiarity)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 55 publications
0
29
1
Order By: Relevance
“…Building on this work, it has been found that some of the performance improvements due to individual experience are only realized at the particular organization (Huckman and Pisano 2006), for the particular task (KC and Staats 2012), or for the particular customer (Clark et al 2013), with which the experience was acquired. Similarly, studies have found that diversity in prior tasks (Boh et al 2007), customers (Clark et al 2013, Huckman andStaats 2011), and partners (Akşin et al 2018, Kim et al 2018 can impact performance.…”
Section: Drivers Of Worker Performance In Operational Systemsmentioning
confidence: 91%
See 2 more Smart Citations
“…Building on this work, it has been found that some of the performance improvements due to individual experience are only realized at the particular organization (Huckman and Pisano 2006), for the particular task (KC and Staats 2012), or for the particular customer (Clark et al 2013), with which the experience was acquired. Similarly, studies have found that diversity in prior tasks (Boh et al 2007), customers (Clark et al 2013, Huckman andStaats 2011), and partners (Akşin et al 2018, Kim et al 2018 can impact performance.…”
Section: Drivers Of Worker Performance In Operational Systemsmentioning
confidence: 91%
“…This is the most divergent and unpredictable sub-process of the activation, in the sense that the process steps themselves are unpredictable. Ambulance crews encounter a host of clinical and non-clinical issues which the crew must resolve together, usually under challenging circumstances and without any external support (Akşin et al 2018, Shostack 1987. As a result the crew cannot follow a standard operating procedure at the scene, but must rely on their decision-making abilities in choosing the best course of action for each incident.…”
Section: Ambulance Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…These two-person crews are not fixed, i.e., crew partners are not permanent. Instead they reflect a “fluid team” in which a crew consists of two flight nurses working together temporarily (generally for the duration of a single shift) to accomplish their work before handing off to the next crew at the end of the shift (similar to emergency medical crews; see Akşin et al, 2021). On a given shift, a flight nurse thus sees and interacts not only with their partner on that particular crew but also the outgoing and incoming crews at the same base (i.e., at shift changes occurring at the beginning and end of the shift, respectively), as well as potentially interacting with the crew working at the other base during the same shift hours (either by phone or in person).…”
Section: Methodsmentioning
confidence: 99%
“…The literature on team experience (sometimes team familiarity) has similarly established that the cumulative number of times a team has jointly completed a task does impact performance (Reagans et al 2005, Huckman et al 2009, Akşin et al 2020). In addition, Staats (2012) finds that the impact of team experience on performance can depend on whether the joint experience is acquired in the same geographic location and whether roles have been changed on the team.…”
Section: Literature Summarymentioning
confidence: 99%